NATUS EX MARIA VIRGINE - Fandy Handoko Tanujaya (STT Amanat Agung, 2014)
The purpose of this essay is to show that in spite of common objections, the doctrine of virgin birth is the only possible interpretation, inference and implication of what the Bible says, especially in the birth narratives. In other words, the doctrine is biblically or canonically necessary. Nevertheless, it will be argued that the doctrine is not metaphysically necessary: God can use other ways to bring about the incarnation while keeping the divinity, humanity, and sinlessness of Jesus Christ. Instead of defending the doctrine as metaphysically necessary, it is more fruitful to proclaim it as biblically fitting. Three theologians who see the doctrine as biblically fitting will be expounded (Irenaeus, Anselm, and Thomas Aquinas), followed by suggestion to establish criteria for good biblical fittingness, partly by cultivating Christian imagination and a sense of divine mystery.